2015
DOI: 10.1002/acn3.245
|View full text |Cite
|
Sign up to set email alerts
|

Chronic enzyme replacement therapy ameliorates neuropathology in alpha‐mannosidosis mice

Abstract: ObjectiveThe lysosomal storage disease alpha‐mannosidosis is caused by the deficiency of the lysosomal acid hydrolase alpha‐mannosidase (LAMAN) leading to lysosomal accumulation of neutral mannose‐linked oligosaccharides throughout the body, including the brain. Clinical findings in alpha‐mannosidosis include skeletal malformations, intellectual disabilities and hearing impairment. To date, no curative treatment is available. We previously developed a beneficial enzyme replacement therapy (ERT) regimen for alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Storage material was prepared for mass spectrometry analysis as previously described ( Damme et al, 2015 ). Briefly urine samples and water extracts of TLC-isolated compounds were centrifuged at 14,000 g for 20 min, and 10 µl of extract were mixed with 10 µl of a 0.01 nmol/µl maltotriose internal standard.…”
Section: Methodsmentioning
confidence: 99%
“…Storage material was prepared for mass spectrometry analysis as previously described ( Damme et al, 2015 ). Briefly urine samples and water extracts of TLC-isolated compounds were centrifuged at 14,000 g for 20 min, and 10 µl of extract were mixed with 10 µl of a 0.01 nmol/µl maltotriose internal standard.…”
Section: Methodsmentioning
confidence: 99%
“…As a next step, we studied the uptake and processing of rhCTSD in CTSD-deficient mice (ctsd -/-). For this purpose, a range of enzyme concentrations was firstly tested taking into account previous studies with other recombinant lysosomal enzymes (not shown) [18][19][20]. Based on these preliminary tests, we decided to give postnatal day 20 (P20) ctsd -/animals a dose of 25 mg/kg of rhCTSD by intravenous (i.v.)…”
Section: Uptake Of Rhctsd In the Cln10 Mouse Modelmentioning
confidence: 99%
“…ERT aims to replace the defective hydrolase by a recombinantly produced enzyme, typically administered by intravenous injection and delivered to the lysosomes via receptor-mediated endocytosis. We have previously developed an ERT strategy to treat αmannosidosis, a LSD caused by the deficiency of the lysosomal acid hydrolase MAN/α-mannosidase [18][19][20]. The treatment of patients with the engineered human MAN/α-mannosidase (velmanase alfa) has been recently approved in Europe [21].…”
Section: Introductionmentioning
confidence: 99%
“…High doses are probably necessary because the injected enzyme is quickly captured by visceral organs and thus the bioavailability of the enzyme is rapidly reduced. Recently, to overcome the immunological problems associated with ERT in alpha-mannosidosis mice, an immune-tolerant mouse model of alpha-mannosidosis was generated [ 66 ]. This mouse model allowed for an evaluation of the effect of high-dose long-term ERT on CSF pathology using rhLAMAN.…”
Section: Enzyme Replacement Therapymentioning
confidence: 99%